(untitled) (International Journal of Current Engineering and Technology, 2014)
Increasing brain performance will be boon to humanity and it has always been a desire to whole mankind to be happy and contented with what they possess but due to human psychology we hardly find someone who is happy with their life. Rather we find people with tensions, depressions, mentally unstable within their daily life. Apart from that many researches have carried on lie detection so far but none found to be fruitful. This paper is an innovative proposal and virtual thought on Predicting and Restoring the Desired Ambience of Mind. The proposal is about recording internal brain minute voltages of a person at jubilant conditions and restoring these voltages by applying external stimulus to the brain to desired condition. The Brain Centers & Afferent Nerves act as mediator for DAMPAR which can also be used for tracing liars.